Can Cognitive Ability Give Invasive Species the Means to Succeed? A Review of the Evidence - Szabo, Birgit; Damas-Moreira, Isabel; Whiting, Martin J. (Frontiers in Ecology and Evolution, 2020)
Invasive species are a global conservation problem that have an enormous economic cost. Understanding the attributes of invasive species and what makes them successful at colonising and flourishing in novel environments is therefore essential for preventing and ameliorating their negative impact. Learning ability and behavioural flexibility—the ability to adjust behaviour flexibly when conditions change including to learn to solve novel problems or existing problems in a novel way, are thought to play a key role during invasions although cognitive ability is rarely considered in studies of invasive species. We begin by reviewing the evidence that flexible learning and problem solving can influence invasion success in both invertebrates and vertebrates. We also review brain size as an index of cognitive ability with respect to invasion success. We then focus on the specific attributes of cognition that are likely to be important for species entering novel environments as they learn the location of resources (e.g. food, shelter), and as they encounter and interact with conspecifics, heterospecifics, and potential predators. We suggest that enhanced spatial learning ability in conjunction with behavioural flexibility are likely to be adaptive. Furthermore, good memory retention and the ability to learn from others (both conspecifics and heterospecifics) are beneficial. Finally, we suggest future directions for studying the link between cognition, fitness, and invasion success. Studies of closely related ‘invasive’ and ‘non-invasive’ species, as well as invasive populations and their source, should provide important baseline information about the potential role of cognitive ability in determining invasion success. We also advocate an experimental approach. In particular, we borrow methods from experimental evolutionary ecology. We suggest that experimental studies in which potential invasive species can be assayed for behaviour and their cognitive ability measured prior to population-level release on small islands will help inform us about the potential role of cognitive ability in determining the fitness of invasive species. The idea that cognitive ability may determine invasion success is only now starting to gain traction. This is a rich field worthy of further study that will help us better understand what makes a successful invasive species.